2018
DOI: 10.1001/jamapsychiatry.2018.2119
|View full text |Cite|
|
Sign up to set email alerts
|

Emotional and Behavioral Symptom Network Structure in Elementary School Girls and Association With Anxiety Disorders and Depression in Adolescence and Early Adulthood

Abstract: The onset of adult psychopathologic disorders can be traced to behavioral or emotional symptoms observed in childhood, which could be targeted in early interventions to prevent future mental disorders. The network perspective is a novel conceptualization of psychopathologic disorders that could help to identify target symptoms with a distinct role in the emergence of mental illness. OBJECTIVE To assess whether the network structure of emotional and behavioral symptoms among elementary school girls is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 55 publications
4
62
1
Order By: Relevance
“…We studied 5,616 college students in terms of the propagation patterns of perceived verbal abuse components and found possible directed relationships that hypothetically could propagate from the perceived verbal abuse to the psychomotor changes and irritability 134 . Further, graph theory metrics calculated from the intra-individual covariance networks demonstrated the hubness of some forms of verbal abuse including ‘damaged self-esteem’ and ‘unjust blame’; the hubs served as shortcuts connecting different ‘verbal abuse-depressive mood-anxiety-social interaction’ features.…”
Section: Resultsmentioning
confidence: 99%
“…We studied 5,616 college students in terms of the propagation patterns of perceived verbal abuse components and found possible directed relationships that hypothetically could propagate from the perceived verbal abuse to the psychomotor changes and irritability 134 . Further, graph theory metrics calculated from the intra-individual covariance networks demonstrated the hubness of some forms of verbal abuse including ‘damaged self-esteem’ and ‘unjust blame’; the hubs served as shortcuts connecting different ‘verbal abuse-depressive mood-anxiety-social interaction’ features.…”
Section: Resultsmentioning
confidence: 99%
“…Connectivity tends to be consistent across time (e.g. Curtiss, Ito, Takebayashi, & Hofmann, 2018; Rouquette et al, 2018; von Stockert, Fried, Armour, & Pietrzak, 2018) and demographic groups, especially gender and age (e.g. Belvederi Murri, Amore, Respino, & Alexopoulos, 2018; Fonseca-Pedrero et al, 2018; Russell, Neill, Carrion, & Weems, 2017); though differences have been observed between countries (Fonseca-Pedrero et al 2018; Wusten et al 2018).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…An examination of maternal depression as symptoms allows for a deeper understanding of the heterogeneity in how the symptoms affect each other. Moreover, knowing how central symptoms change informs on the reasons underlying different trajectories and etiological profiles ( 38 ) of psychopathology across the peripartum period, thus informing intervention programs.…”
Section: Introductionmentioning
confidence: 99%